Pemakaian Metode ASME PTC 4.1 Pada Evaluasi Performa (Efisiensi) Boiler Pulverized Firing di Pembangkit Listrik Tenaga Uap (PLTU) - Edy Sarwono; Indra Saputra (Radial : Jurnal Ilmiah Sains dan Rekayasa, 2023)
The rankine cycle is widely used for thermal generators that use steam as a turbine driver in power generation plant. There are 4 main equipments in power plant with rankine cycle system that is: Boiler, Turbine, Condenser and Feed pump. Boiler is a tool to heat water up to steam with high temperature and pressure. Then steam goes into the turbine to drive the generator. The steam coming out of the turbine is cooled inside the condenser to be changed into liquid again. Condenser coolers are widely used in steam power plants is sea water, but some are using river water. Water becomes a working fluid in the rankine cycle and undergoes closed cycle (close loop cycle) meaning continuously water at the end of the cycle process re-entry to the early process cycle. There are several methods to calculate boiler efficiency by direct method (input method) and heat loss method (energy balanced method). The calculation by the direct method by dividing the resulting steam energy divided by the fuel energy coming into the boiler. While the calculation of boiler efficiency with heat loss method is the fuel energy that enter the boiler reduced by losses that occur in the boiler. ASME PTC 4.1 method can be used to calculate boiler efficiency at large boiler capacity, so PTC 4.1 method is often used to evaluate boiler in power plant. The ASME PTC 4.1 method is recommended for the calculation of heat-loss methods in the boiler and is often performed to review the efficiency according to the design as a benchmark.